Evolution and significance of banking distribution channels - Marcin Jóźwiak (Finanse i Prawo Finansowe)
The purpose of the article. The aim of this article is to present and evaluate the distribution channels used by retail banks, the determinants of banks' choice of these channels, and the directions of changes. The study will seek to answer the research question of what the evolution of distribution channels for banking products and services entails and what determines it.